2003
DOI: 10.2116/analsci.19.1477
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polyaniline/Sol-Gel Derived Tetraethylorthosilicate Films to an Amperometric Lactate Biosensor

Abstract: Chemical and biochemical sensors are presently the subject of extensive research and development for a wide variety of applications in environmental, industrial and biomedical monitoring. During the recent past, there has been an increasing demand for biosensors towards the determination of clinical parameters in biological fluids, such as blood, urine and serum. In this context, a number of biosensors for the estimation of glucose, urea, lactate, cholesterol etc. have been developed. [1][2][3][4][5] Lactate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Among the various conducting polymers, polyaniline [4,5,10,27,28] has attracted much attention because of its ease of synthesis, extraordinary stability and unique redox characteristics. Besides this, the control over the shape and dimensions of polyaniline [29] by varying synthesis or processing conditions is likely to result in desired physical and electrochemical properties for biosensing application.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various conducting polymers, polyaniline [4,5,10,27,28] has attracted much attention because of its ease of synthesis, extraordinary stability and unique redox characteristics. Besides this, the control over the shape and dimensions of polyaniline [29] by varying synthesis or processing conditions is likely to result in desired physical and electrochemical properties for biosensing application.…”
Section: Introductionmentioning
confidence: 99%
“…Further, addition to the starting sol of polymers, e.g., poly-dimethyl-siloxane, polyamides, polyacrylates, polyethylene glycol (PEG), and poly(ethylene-oxide), was investigated to regulate the inorganic condensation–polymerization process [130]. Polyaniline (PANI) was electrochemically entrapped onto TEOS-derived films on indium tin oxide (ITO) coated glass to immobilize lactate dehydrogenase (LDH) for lactate sensing [135]. Acetylcholinesterase (AchEs) enzyme in TMOS+MTMOS+PEG-derived sol-gel has been immobilized on a modified screen printed electrode for the detection of carbamate insecticides [136].…”
Section: Molecular Recognition For Biosensorsmentioning
confidence: 99%
“…Singhal et al have reported Langmuir-Blodgett films of poly(3-hexyl thiophene) prepared by simultaneous entrapment of glucose oxidase and transferred onto the indium tin oxide-coated glass plates [159]. Chaubey et al have reported the electrochemical entrapment of polyaniline (PANI) onto sol-gel derived tetraethylorthosilicate (TEOS) films deposited onto indium tin oxide (ITO) coated glass utilized for immobilization of lactate dehydrogenase (LDH) for the lactate measurement [160]. Arya et al obtained ChOx/FANB/ODT/Au selfassembled monolayer based bioelectrode to estimate cholesterol by surface plasmon resonance technique [161].…”
Section: Enzymosensorsmentioning
confidence: 99%